(untitled) (Bangladesh Journal of Agricultural Research, 2012)
Field survey based laboratory studies were carried out to investigate trace elements contents in soils and vegetables collected from industrially polluted and non-polluted areas. The content of four trace elements, such as manganese (Mn), iron (Fe), copper (Cu), and zinc (Zn) in four popular vegetables, namely spinach (Spinacia oleracea), red amaranth (Amaranthus tricolor), bottle gourd (Lagenaria vulgaris), and pumpkin (Cucurbita moschata) and the rizosphere soils of the respective crops were collected from three locations viz. i) directly polluted (Kaliakoir, Konabari, Gazipur), ii) indirectly polluted (Zorun, Konabari, Gazipur), and iii) non-polluted (BARI, Gazipur) areas. In all four vegetables, a similar trend in metal contents was observed i.e. directly polluted>indirectly polluted>non-polluted. The Mn and Fe concentrations were found in the order of spinach>red amaranth>bottle gourd>pumpkin, whereas it was little bit irregular pattern for Zn. The Cu concentration was higher in spinach followed by red amaranth and the least in bottle gourd irrespective of the location. Mean concentration of Mn, Fe, and Cu in vegetables from investigated areas were below the recommended level except Zn. However, the higher concentrations of Mn, Fe, Cu, and Zn in the polluted (either directly or indirectly) area indicates that industrial activities, such as discharge their wastes and effluents into the natural ecosystems in most cases without any treatment, thus causing health hazard as well as environmental pollution, especially with heavy metals and organic toxic. Bangladesh J. Agril. Res. 37(3): 515-527, September 2012 DOI: http://dx.doi.org/10.3329/bjar.v37i3.12128